УМАЙ АНА ОБРАЗЫНДА ҚУС КУЛЬТИНИҢ СӘЎЛЕЛЕНИЎИ - Зарипова, З. (FAN va JAMIYAT, 2023)
The article tells about the character of the goddess Umai, which is known in the mythology of the Turkic-speaking peoples, which is described in the character of a mythological bird. At the same time, examples are given about the fetish of the bird cult.